Characteristics and Praxis of Tumang Metalcraft Cultural Production - Mardi, Mardi; Ibnan Syarif, Muh.; Syakir, Syakir (Catharsis, 2021)
The existence of metalcraft in Tumang village which still exists until now has become part of the life of the local community there. This makes the metalcraft as a cultural product. It means that the metalcraft have a certain place in the social production, circulation, and consumption. This study aims to analyze the establishment of cultural products of metalcraft in Tumang village. This study used a qualitative method with a phenomenological approach. The data analysis was carried out after the data collection. The data collection was conducted by observation, interviews, and document studies. The data analysis used phenomenological model analysis. The results of this study indicate that the characteristics of Tumang metalcraft can be seen through its manufacturing technique, namely mbabar process.The cultural production in Tumang metalcraft was formed from the meeting of several agents. The meeting of agents is controlled and supported by habitus, capital, and strategy so that they can compete in the field of cultural production. Through this competition, the agents who have strong capital will maintain their social positions so that they become the dominating party. Meanwhile, the agents whose capitals are weak or dominated will struggle by means of resistance. The resistance is done by creating a new view of the world so that they can struggle in the production field of Tumang metalcraft.